Features of the Course of Covid-19 in Patients with Cardiovascular Pathology - Kodirova Shahlo Salomovna (Scholars Digest Publishing, 2023)
The interest of the world community today is drawnto one global problem - the new coronavirus infection COVID-19 (Coronavirus Disease 2019) caused by the SARS-CoV-2 virus [1,2]. It should be noted that among all comorbid conditions, cardiovascular diseases (CVD) are a significant medical and social problem, regardless of the pandemic [5]. Therefore, it is hardly surprising that patients with concomitant CVD make up a significant proportion of patients infected with the SARS-CoV-2 virus.